(untitled) (Bangladesh Heart Journal, 2016)
Background: Open mitral operation in patients with massive left atrial thrombus still with high mortality due to intra-operative embolism. To prevent this mortality due to intra-operative embolism and to prevent this danger we practiced a surgical technique which includes careful handling of heart and obliteration of left ventricular cavity by bilateral compression. Method: We used this technique in patients of severe mitral stenosis with atrial thrombus during mitral valve replacement. Our technique was to obliterate the left ventricular cavity and thus keep the mitral cusps in a coapted position by placing gauge posterior to left ventricle and a compression over right ventricle by hand of an assistant with a piece of gauze. This obliteration prevented passage of fragments of left atrial thrombus towards collapsed left ventricle. Result: Before practicing this technique, 4 out 9 patients expired due to cerebral embolism . But after implementation of this technique in 17 patients no mortality or morbidity occurred. Conclusion: This technique of removal of left atrial thrombus during mitral valve replacement may be a safe procedure for preventing peroperative embolism. Bangladesh Heart Journal 2016; 31(1) : 26-28